Emesis to trichothecene deoxynivalenol and its congeners correspond to secretion of peptide YY and 5-HT - Wei, Ben; Xiao, Huiping; Xu, Baocai; Kuca, Kamil; Qin, Zihui; Guo, Xinyi; Wu, Wenda; Wu, Qinghua (Food and chemical toxicology, 2023)
The type B trichothecenes pollute food crops and have been associated to alimentary toxicosis resulted in emetic reaction in human and animal. This group of mycotoxins consists deoxynivalenol (DON) and four structurally related congeners: 3-acetyl-deoxynivalenol (3-ADON), 15-acetyl deoxynivalenol (15-ADON), nivalenol (NIV) and 4-acetyl-nivalenol (fusarenon X, FX). While emesis induced by intraperitoneally dosed to DON in the mink has been related to plasma up-grading of 5-hydroxytryptamine (5-HT) and neurotransmitters peptide YY (PYY), the impact of oral dosing with DON or its four congeners on secretion of these chemical substances have not been established. The aim of this work was to contraste emetic influence to type B trichothecene mycotoxins by orally dosing and involve these influence to PYY and 5-HT. All five toxins attracted marked emetic reaction that are relevant to elevated PYY and 5-HT. The reduction in vomiting induced by the five toxins and PYY was due to blocking of the neuropeptide Y2 receptor. The inhibition of the induced vomiting response by 5-HT and all five toxins is regulated by the 5-HT3 receptor inhibitor granisetron. In a word, our results indicate that PYY and 5-HT take a key role in the emetic reaction evoked by type B trichothecenes.
Keywords: Animals; Mycotoxins; Mycotoxin; Serotonin; norek; lidé; serotonin; peptid YY; 5-HT; Trichothecenes, Type B; mykotoxiny; Vomiting; Mink; Humans; Trichothecenes; zvracení; Trichothecene; Emesis; trichotheceny typu B; trichotheceny; emetika; zvířata; Peptide YY; Emetics